Steady three-dimensional patterns in gravity-driven film flow down an inclined sinusoidal bottom contour - Al-Shamaa, Bashar; Kahraman, T.; Wierschem, Andreas (Physics of Fluids, 2023)
We experimentally studied gravity-driven film flow in an inclined corrugated channel. Beyond a critical Reynolds number, three-dimensional patterns appear. We identified two different types of patterns: a synchronous and a checkerboard one. While the synchronous pattern appears at all inclination angles studied, we observed the checkerboard one only at higher inclination angles and Reynolds numbers. The patterns suppress traveling waves and stabilize the steady flow. We characterize the patterns and their generation and provide a flow-regime map.
CRIS-Team Scopus Importer:2023-03-24